People's Movements in the 21st Century - Risks, Challenges and Benefits 2017
DOI: 10.5772/66949
|View full text |Cite
|
Sign up to set email alerts
|

The Voice of Trailing Women in the Decision to Relocate: Is it Really a Choice?

Abstract: The reasons for migration among highly skilled couples are economic as well as noneconomic. However, our understanding of the motivations of trailing wives remains somewhat limited, especially given their loss of personal, professional, and social resources during the relocation. This chapter explores the motivations of women to relocate for their husband's work. It examines how gender ideologies weave with the decision to relocate, and how women's considerations and preferences are taken into account during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Conversely, other studies indicated that spouses/partners' professional concerns and career orientations had limited impact on the decision to expatriate (Braseby, 2010;Dupuis et al, 2008). As identified in these studies, because of gender-role forces and ideologies, spouses/partners prioritized family needs and supported IAs because of economic opportunities, to advance the husband's career, to improve family and children's well-being and as a result of work/career dissatisfaction (Braseby, 2010;Gupta et al, 2012;Slobodin, 2017).…”
Section: Literature Reviewmentioning
confidence: 94%
See 1 more Smart Citation
“…Conversely, other studies indicated that spouses/partners' professional concerns and career orientations had limited impact on the decision to expatriate (Braseby, 2010;Dupuis et al, 2008). As identified in these studies, because of gender-role forces and ideologies, spouses/partners prioritized family needs and supported IAs because of economic opportunities, to advance the husband's career, to improve family and children's well-being and as a result of work/career dissatisfaction (Braseby, 2010;Gupta et al, 2012;Slobodin, 2017).…”
Section: Literature Reviewmentioning
confidence: 94%
“…As identified in these studies, because of gender-role forces and ideologies, spouses/partners prioritized family needs and supported IAs because of economic opportunities, to advance the husband’s career, to improve family and children’s well-being and as a result of work/career dissatisfaction (Braseby, 2010; Gupta et al. , 2012; Slobodin, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A desk review of the current literature highlights a number of common themes across the scholarship. Building upon the psychosocial and sociocultural approaches to exploring repeat mobility, the question of identity disruption is widely researched, notably amongst accompanying spouses (see for example Bernard 2014;Slobodin 2019;2017;Suter and Cangià 2020). Similarly, the impact of sociocultural transitions on expatriate children is also broadly investigated (see Gyger Gaspoz 2013; Van Der Zee et al 2007;Warinowski 2019).…”
Section: Introductionmentioning
confidence: 99%